Halal Tourism Based on Value Creation - Ratnasari, Ririn Tri (al-Uqud : Journal of Islamic Economics, 2020)
Nowadays, halal tourism product is not only focused on Muslim tourists, but also non-Muslim one. The halal tourism industry needs to develop the people understanding of halal values in order to bring benefits to consumers through recognition of the tourism management potency as well as the need of value identification. This research aimed to develop value-based tourism, identify the value types, as well as create value as the basis for managing lawful tourism, which needs a model to facilitate recognizion of the tourism product excellence. This research used qualitative case study approach, with the head of tourism in the region where has potency to implement Islamic Marketing Concept as the key informants. The result showed that halal marketing included not only about product but also about pricing, promotion, and place. Muslim consumers were keen on tourism services that implement lawful approach. Furthermore, there were ten values of tourism in Indonesia e.g. Religious Tourism, Geo Tourism, Natural Tourism, Fashion Tourism, Culinary Tourism, Medical Tourism, Historical Tourism, Sport Tourism, Culture Tourism, and Hospitality Tourism.